2016
DOI: 10.1093/nar/gkv1546
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal transformation inBacillus subtilisis a non-polar recombination reaction

Abstract: Natural chromosomal transformation is one of the primary driving forces of bacterial evolution. This reaction involves the recombination of the internalized linear single-stranded (ss) DNA with the homologous resident duplex via RecA-mediated integration in concert with SsbA and DprA or RecO. We show that sequence divergence prevents Bacillus subtilis chromosomal transformation in a log-linear fashion, but it exerts a minor effect when the divergence is localized at a discrete end. In the nucleotide bound form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
77
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(83 citation statements)
references
References 69 publications
(127 reference statements)
6
77
0
Order By: Relevance
“…S3 for details. This result is in agreement with previous work (14, 15). In our system, the dependence on sequence similarity already generates a significant variation of transfer rates independently of selection on specific genes.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…S3 for details. This result is in agreement with previous work (14, 15). In our system, the dependence on sequence similarity already generates a significant variation of transfer rates independently of selection on specific genes.…”
Section: Resultssupporting
confidence: 94%
“…The efficiency of the DNA uptake machinery is a major determinant of the probability of transformation (11). At the level of recombination, this probability decreases exponentially as a function of the local sequence divergence, likely because nucleotide mismatches suppress sequence pairing at the initiation of the recombination step (1416). As shown in a recent study, laboratory experiments can induce genome-wide transformation between close lineages (17).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these factors are specific for genetic recombination, for recombinational repair, or for both ( 3 ). During genetic recombination, the accessory proteins that act before homology search can again be divided into those that promote (DprA, RecO[R]), limit RecA (SsbA, SsbB) or activate RecA nucleation to catalyze DSE in the presence of adenosine triphosphate (ATP) (SsbA and DprA or RecO[R], two-component mediators ( 9 , 10 , 15 17 ). The proteins that act during homology search are RecX and RecU ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…In their ATP-bound form, these recombinases can nucleate on protein-free ssDNA, but they cannot catalyze DSE in the absence of accessory factors (inactive RecA) ( 10 , 32 – 34 ). Unlike RecA Eco ·ATP ( 11 – 13 ) or RecA·dATP ( 32 , 35 ), RecA·ATP cannot nucleate or polymerize in the SsbA– or SsbB–ssDNA complexes ( 10 , 16 , 17 , 36 ). The presence of DprA reverses the negative effect of SsbA or SsbB on RecA filament growth, and DprA–SsbA are necessary and sufficient to activate RecA·ATP to catalyze bidirectional DSE, with greater efficiency in the 5′→3′ direction ( 10 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Physiological roles of both these proteins have been under extensive investigation for over a decade, and they are currently known to participate in DNA replication (2), recombination (3), damage repair (4) and the process of transformation of the B. subtilis chromosome in the state of natural competence (5). We have previously reported that B. subtilis SsbA and SsbB can undergo phosphorylation at tyrosine residues, and this phosphorylation is catalyzed by the B. subtilis BY-kinase PtkA (6).…”
mentioning
confidence: 99%